Characterization of innate immune response to hepatitis B virus genotype F acute infection in tree shrew (Tupaia belangeri) model - Kayesh, Mohammad Enamul Hoque; Hashem, Md Abul; Sanada, Takahiro; Kitab, Bouchra; Rashid, Md Haroon Or; Akter, Lipi; Ezzikouri, Sayeh; Murakami, Shuko; Ogawa, Shintaro; Tanaka, Yasuhito; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Virology, 2022)
Hepatitis B virus (HBV) infection is a global public health problem. The clinical outcomes of HBV infections are influenced by host as well as viral factors, including viral genotypes and subgenotypes. The interplay between HBV and host innate immunity remains unclear because of the lack of a suitable small animal model. Tree shrews (Tupaia belangeri) have been utilized as a useful animal model for hepatitis viruses such as hepatitis B and C viruses. In this study, we characterized acute infections by HBV genotype F (HBV-F) wild type (Wt) and mutant type (Mt) viruses in adult tree shrews. Serum alanine aminotransferase levels were measured before and post- infection 7 and 14 dpi. Both HBV-F-Wt and Mt were detected in the HBV-F-infected tree shrew serum and liver tissue at 7 and 14 dpi. We examined the intrahepatic expression patterns of Toll-like receptors (TLRs) (TLR1–9 mRNAs), cGAS, several transcription factors such as STAT1, STAT2, IRF7, HNF4, PD-L1, and cytokines, including IFN-β, IFN-γ, IL-6, and TNF-α in HBV-F Wt/Mt-infected tree shrews. When compared with uninfected animal group, significant suppression of TLR8 in HBV-F-Wt infected animals and significant suppression of PD-L1 in both HBV-F-Wt and Mt infected animals were observed. Thus, tree shrew can be a useful animal model to characterize HBV-F pathogenesis.